EMPOWERMENT OF URBAN FARM WOMEN IN SUPPORTING THE IMPROVEMENT OF THE FAMILY ECONOMY WITH LAND USE OF YARDS: PEMBERDAYAAN WANITA TANI KOTA DALAM MENDUKUNG PERBAIKAN EKONOMI KELUARGA DENGAN PEMANFAATAN LAHAN PEKARANGAN - Indarwati Indarwati; Dwie Retna S; Jajuk Herawati; Tatuk Tojibatus S (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2021)
Peasant Women Kota has the potential as a driving force for urban community empowerment. The position of women who have been in the kingdom with men has a considerable share in supporting economic improvement. The reluctance of urban peasant women in productive activities is caused, among others, by a lack of knowledge to work, a lack of motivation to move in productive economic activities, and the lack of introduction of The Application of Some Appropriate Technology that they can actually do. There are many productive economic activities that can be done;  To fill your free time while taking care of the household.  Productivity of the concentration of yard land / land around the place of residence is often forgotten. The productivity of yard land use is one solution. The purpose of the activity is "Empowerment of Women Farmers City with land use of yards. Team faculty of agriculture Univ. Wijaya Kusuma Surabaya as a Companion in the Peasant Women's Group "Pinasti Arum" in the Dukuh Kupang area of Surabaya in the framework of the implementation of the Science and Technology program for the Community (IbM) has provided counseling, training and introduced innovation / Appropriate Technology in the field of Urban Agriculture, so that the Mitra Perempuan Tani Kota group in the Dukiuh Kupang area of Surabaya can independently manage narrow yard land,  Narrowly, bero land / sleeping land around the residence in hopes of adding economic value to the family, and can increase the income of families and farming groups in particular. In mentoring activities instead of the delivery of problem material; but also emphasized on changes in social behavior will be the importance of togetherness in community. The delivery of the material is more emphasized on the goal of empowerment of partner groups in an integrated way. From the results of the evaluation during the implementation of community service activities (IbM) seen: (1) changes in partner behavior is better, more familiar, the sense of togetherness in the group is increased;  between before the implementation of the IbM program with after the implementation of assistance. (2) The Peasant Women's Group more controlled TTG Agricultural Land narrowly. (3) The Farmer Group can overcome household organic waste for mol liquid fertilizer manufacturing materials (4) Partner Groups have grown entrepreneurial souls. (5) Members of the Peasant Women group are more motivated to utilize the yard land (6) The Environmental Situation of the Peasant Women's Group becomes more organized, green, clean and beautiful. (7) Synergy of Universities and Government plays a role in Community Empowerment